Satisfaction and experiences of patients taking fingolimod and involved in a pharmacy-based patient support program in Switzerland - a qualitative study - Aline Bourdin; Julie Dubois; Rose-Anna Foley; Myriam Schluep; Olivier Bugnon; Jérôme Berger (BMC, 2020)
Abstract Background Fingolimod is an oral multiple sclerosis drug that is considered a specialty drug due to its high cost and safety issues. The Fingolimod Patient Support Program (F-PSP) is a specialty pharmacy service developed to ensure the responsible use of fingolimod by promoting patient safety and medication adherence. This study aims to explore the satisfaction, experiences and perceptions regarding the F-PSP among patients currently involved in this program or recently withdrawn. Methods A qualitative study was conducted via individual, face-to-face semistructured interviews with patients involved in the F-PSP. The interviews were audio-recorded, transcribed verbatim, coded and analyzed via thematic content analysis. Results The main themes identified from the interviews (n = 17) were overall perception of the F-PSP, perception of the pharmacist-led consultations, perception of the tools (electronic monitor and drug intake graph), reasons to participate or potentially withdraw, and suggestions for improvements. Participants perceived the F-PSP as a reassuring support that complemented their medical care, providing a more human, personalized and person-centered approach than usual pharmacy care. Pharmacist-led consultations were valued for the medication-related and holistic support they provided. The importance of the pharmacist's attitude was emphasized. The electronic monitor was valued for promoting daily medication adherence and allowing the involvement of relatives, which reassured participants and their relatives. The participants appreciated the drug intake graph because it provided an objective overview of medication adherence, thereby reassuring, rewarding, and motivating them. The main reason to join the program was to be supported, especially with respect to medication adherence. Conclusions Participants were satisfied with the F-PSP, each for different reasons. Their feedback enabled the identification of measures for the optimization of the F-PSP and should facilitate its dissemination and transfer to other drugs/diseases/populations. Essential elements of generic pharmacist-led patient support programs considered valuable from the patients' perspective were identified.